Using the aeromagnetic data for mapping the basement depth and contact locations, at southern part of Tihamah region, western Yemen - Marwan A. Al-Badani; Yahia M. Al-Wathaf (Egyptian Journal of Petroleum)
The present study aims to produce an excellent picture for the basement depth and contact locations, deduced from the available aeromagnetic data. The total intensity aeromagnetic map was first corrected by the application of the reduction to the magnetic pole (for low latitude areas) technique. On the other hand, this map shows different anomalies of varying frequencies and amplitudes that reveal various causative sources, as well as varying compositions and depths. So, the fast Fourier transform is applied on the RTP map to show the regional and residual sources and their depths, using the radial averaged power spectrum which divided into three segments, according to the slope,: the maximum depth is 12,500 m that probably reflect the crustal thickness at this place, depths of deep sources which reflect the maximum depth to the basement complex is found to be 10,388 m and the shallow sources and noise (near-surface geological structures), its depth will be 2410 m. This slope probably represents the minimum depth to the basement, especially at the eastern part of the study area (along the great escarpment). At the western part, the basement will be deeper than the eastern part. Different edge detection processes, for example, tilt angle derivative (TDR) and its total horizontal derivative (HD_TDR) as well as 3D-Euler deconvolution; can determine the edges of these sources. These techniques were carried out on the aeromagnetic data of Tihamah region (the study area). The estimated Euler solutions were plotted on the tilt angle derivative map. An excellent correlation was noticed between these techniques indicating that both of them can be attributed in delineating the general structural framework of the area. These techniques indicated that the southern part of Tihamah region was highly affected by Red Sea–Gulf of Aden rift system, that represent two legs of Afar Triple Junction. Moreover that, two depth methods were applied, analytic signal (AS) and source parameter imaging (SPI). They reflected similar results for estimating the basement depths. From both of them the depth ranges from 2050 to 10,885 m. On the other hand, all the methods used in this study gave a similar results to the depth of the basement rocks, ranging in depth between 2250and 10,400 m. Keywords: Basement, Power spectrum, Tilt-depth, TDR, THDR_TDR, 3D-Euler, AS, SPI, Magnetic data, Tihamah plain, Yemen, Afar Triple Junction